Analysis of The Internal Quality Assurance System at Pangudi Luhur Bintang Laut Surakarta Middle School - Wiyartiningtyas, Lintang Pramusita; Kurniawati, Destriana (Universitas Sebelas Maret, 2025)
Education is a lifelong learning experience, which has a positive influence on individuals. Education management requires the implementation of a quality assurance system, which is implemented through six stages of the internal quality assurance cycle, consisting of: (1) quality mapping, (2) preparation of a fulfillment plan, (3) implementation of quality fulfillment, (4) evaluation, and (5) preparation of standards. In research to determine the internal quality assurance system (SPMI) at SMP Bintang Laut Surakarta, the method used was a qualitative approach with descriptive methods, which began with interviews, documentation, and descriptions of research data. Based on the research that has been carried out, SMP Bintang Laut Surakarta has implemented an Internal Quality Assurance System, by the SPMI cycles and stages: (1) quality mapping based on School Self-Evaluation (EDS) and DAPODIK, (2) preparation of quality improvement plans through planning mature which includes curriculum, student affairs, infrastructure, human relations, and IT facilities, (3) implementation of a fulfillment plan involving all parties in the school with clear targets, (4) monitoring and evaluation carried out every three months by the deputy principal and at the end of each year by the Pangudi Luhur Foundation, and (5) setting new standards for the 2024/2025 school year which includes the formation of a learning committee for school quality assurance involving the principal, teacher, school committee and parents.